2015
DOI: 10.1097/ico.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

Pythium insidiosum Keratitis

Abstract: P. insidiosum keratitis needs to be considered in the differential diagnosis of severe fungal keratitis. It can be identified using the zoospore formation method and confirmed by ITS DNA sequencing. Lack of response to currently used antifungal drugs calls for evaluation of newer drugs for medical therapy and consideration for early penetrating keratoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…The first case of human subcutaneous pythiosis was reported in Thailand in 1985, and Thailand has the highest incidence of this disease (1). Currently, the increased trend of human pythiosis cases has been revealed not only in Thailand but also in other countries in Asia (2)(3)(4)(5)(6), Australia (7)(8)(9), North America (10), and South America (11). Vascular pythiosis is the most common manifestation of human pythiosis, which almost always occurs in patients with underlying hemoglobinopathy complicated by hemochromatosis (1,(12)(13)(14).…”
mentioning
confidence: 99%
“…The first case of human subcutaneous pythiosis was reported in Thailand in 1985, and Thailand has the highest incidence of this disease (1). Currently, the increased trend of human pythiosis cases has been revealed not only in Thailand but also in other countries in Asia (2)(3)(4)(5)(6), Australia (7)(8)(9), North America (10), and South America (11). Vascular pythiosis is the most common manifestation of human pythiosis, which almost always occurs in patients with underlying hemoglobinopathy complicated by hemochromatosis (1,(12)(13)(14).…”
mentioning
confidence: 99%
“…It appeared at the intermediate stage, along with the presence of dot-like and tentacle-like corneal infiltrates described in Savitri Sharma’s report [18]. The flocculent-like sphacelus covered the ulcer surface and became easier to be observed after application of Natamycin.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, India has been highlighted due to the 9 cases reported in 2015. The researchers from Thailand and India demonstrated that ocular pythiosis may be not as rare as was previously considered, but simply goes unrecognized [2,18]. Briefly, the main reasons for the misdiagnosis of pythiosis include lack of characteristic clinical features, unawareness among clinicians, and a lack of early diagnosis in some regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with Pythium keratitis usually present with typical clinical manifestations, including multiple, linear, tentacle-like infiltrates and dot-like or pinhead-shaped infiltrates, involving the subepithelial, anterior stromal, and midstromal layers in surrounding cornea and radiating in a reticular pattern from the central area of the lesion towards the limbus (Fig. 3) (Lekhanont et al, 2009;Lelievre et al, 2015;Bagga et al, 2018;Chatterjee & Agrawal, 2018;Agarwal et al, 2019;He et al, 2016;Thanathanee et al, 2013;Sharma et al, 2015;Agarwal et al, 2018). Radial keratoneuritis has been observed in some cases (Lekhanont et al, 2009;He et al, 2016).…”
Section: Ocular Pythiosismentioning
confidence: 99%